Identical Pulse Programming Based Ultra-Thin 5 nm HfZrO2 Ferroelectric Field Effect Transistors with High Conductance Ratio and Linearity Potentiation Learning Trajectory. (18th June 2021) - Liao, C.-Y.; Hsiang, K.-Y.; Chang, S.-H.; Chiang, S.-H.; Hsieh, F.-C.; Liu, J.-H.; Liang, H.; Luo, Z.-F.; Lin, C.-Y.; Chen, L.-Y.; Hu, V. P.-H.; Lee, M. H.
Abstract : This study systematically investigates identical pulse stimulation for potentiation machine learning to achieve a linear potentiation non-linearity ( α P ) equal to 1.25 and a high conductance ratio >1, 000x with 5 nm-thick HfZrO2 (HZO) ferroelectric field effect transistors (FeFET). The trade-off characteristics between conductance ratio and linearity are exhibited. The higher remnant polarization (Pr ) for memory window (MW) enhancement leads to an increasing conductance ratio but degrades the non-linearity of the training curve. The optimized stimulation condition for the identical pulse is performed with a pulse width of 50 ns and low access voltage for HZO thicknesses from 15 to 5 nm. These highlighted merits provide an opportunity to integrate emerging devices such as computing-in-memory (CIM) applications in the future.